Ecumenical ecclesiology as a tool for township congregations to facilitate transformation of the (South) African society - K.J. Pali (Acta Theologica)
South Africa is experiencing a proliferation of ecumenical church organisations since the advent of democratic South Africa. Many of these organisations occur in the townships in the form of minister fraternals, some of whom are affiliated to a larger and higher ecumenical body such as SACC and others. Nearly every town in South Africa has a minister fraternal. The goals of these minister fraternals are fellowship, reaching out to each other, and societal involvement to deal with social ills in partnership with other societal structures such as the state and business sectors. This study aims to explore how congregations in the townships (in Mangaung, Bloemfontein, and Qwaqwa), through their local ecumenical organisations, function together to facilitate the transformation of their identity and mission. This empirical study implements a critical theory approach to analyse sources and data used in this study.